Association between the aromatase (CYP19A1) gene variant rs10046 and cardiovascular risk in postmenopausal women - Betânia Rodrigues dos Santos; Gislaine Casanova; Thais Rasia da Silva; Karen Oppermann; Poli Mara Spritzer (Archives of Endocrinology and Metabolism)
ABSTRACT Objective: To assess the genotypic and allelic distribution of the rs10046 polymorphism in the CYP19A1 gene and evaluate whether this aromatase gene variant is associated with cardiovascular risk in postmenopausal women. Materials and methods: This cross-sectional study analyzed repository-stored samples from 370 postmenopausal women aged 44-72 years. Clinical, metabolic, and hormonal data were collected. The patients’ estimated 10-year atherosclerotic cardiovascular disease (ASCVD) risk was calculated using the ASCVD Risk Estimator Plus, as recommended by the American College of Cardiology/American Heart Association. Genotyping of the rs10046 polymorphism of the CYP19A1 gene was carried out using real-time polymerase chain reaction with allelic discrimination assays. Results: The participants had a mean age of 56.07 ± 5.58 years and a mean body mass index (BMI) of 27.73 ± 5.41 kg/m². The 10-year ASCVD risk was estimated to be low, borderline, intermediate, and high in 64.7%, 12.8%, 19.8%, and 2.7% of the participants, respectively. The CC genotype of the rs10046 polymorphism was associated with low estradiol levels (p = 0.003) and high ASCVD scores (p = 0.014). In a multivariate model, age (p < 0.001) and CC genotype (p = 0.021) were independently associated with higher ASCVD risk. Conclusion: The present study found that the CC genotype of the rs10046 polymorphism in the CYP19A1 gene is associated with low estradiol levels and an increased ASCVD risk. Additionally, the results indicated that, among postmenopausal women, age and the CC genotype of rs10046 were associated with a high prevalence of ASCVD risk, independent of BMI.